Fixing Federal Faults. Complementary Member State Policies in Swiss Health Care Policy - Fritz Sager; Christian Rüefli; Eva Thomann (International Review of Public Policy)
This article aims to understand what makes member states complement federal healthcare policy beyond the instruments planned by federal policy. We employ a Multiple Streams approach to study how Swiss member states use their discretion in order to complement federal healthcare regulation with the aim of decreasing outpatient healthcare expenditures at the cantonal level. Based on a written survey in the Swiss cantons, we perform a Fuzzy Set Qualitative Comparative Analysis (fsQCA), which places a keen emphasis on complex patterns. The method identifies what combinations of determinants make it particularly likely that a canton opts for complementary policy activity. Several configurations prove to foster such activity. While this is important, it is also important to pay attention to the constellations that precisely do not foster complementary policy activity. Our analysis of the cantonal choices on governing outpatient healthcare reveals that party politics in the executive and/or the public administration play a major role in this task, whereas neither organized interests within the medical profession nor individual policy entrepreneurs are crucial. Federalist systems offer opportunities for policy innovations the federal level ultimately may benefit from.